Digitalized Ship Maintenance Management System Website Application Innovation Strategy Using Design Thinking Method - Wicaksono, Bayu Mahardika; Pratiwi, Emmy; Wahyurini, Octaviyanti Dwi (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The purpose of the study is to explore the benefits of digitalization, specifically in the context of PT Biro Klasifikasi Indonesia's (PT. BKI) digital transformation efforts. The focus is on how digitalization can enhance operational efficiency, productivity, customer service, and global competitiveness in the maritime industry. Method: The research employs the design thinking method to identify and address customer needs and challenges. It highlights the development of the